2020
DOI: 10.1186/s12961-019-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating evidence from research into decision-making for controlling endemic tropical diseases in South East Nigeria: perceptions of producers and users of evidence on barriers and solutions

Abstract: Background: Endemic tropical diseases (ETDs) constitute a significant health burden in resource-poor countries. Weak integration of research evidence into policy and practice poses a major challenge to the control of ETDs. This study was undertaken to explore barriers to the use of research evidence in decision-making for controlling ETDs. It also highlights potential strategies for addressing these barriers, including the gaps in research generation and utilisation in the context of endemic disease control. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…This engagement afforded an opportunity to reinforce producer-user dialogue, the absence of which is known in the literature to constrain GRIPP. Weak linkages between producers and users of evidence have been reported severally in literature [37][38][39] as a constraint to knowledge translation, and we also found this to be a factor in our study context as reported in the baseline assessment [36]. Studies have shown that when producers of evidence engage end users early enough in the evidence production process, that it facilitates decision making in policy and practice [37,40] In 2003, a study showed strategies to improve stakeholder engagement in LMICs were either not undertaken, or where they were undertaken, were not successful [6], so successfully carrying out this producer-user engagement servers to improve on the necessary task of building a critical mass of producers and users of HPSR evidence for the control of endemic diseases, and for overall health system strengthening in LMICs.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This engagement afforded an opportunity to reinforce producer-user dialogue, the absence of which is known in the literature to constrain GRIPP. Weak linkages between producers and users of evidence have been reported severally in literature [37][38][39] as a constraint to knowledge translation, and we also found this to be a factor in our study context as reported in the baseline assessment [36]. Studies have shown that when producers of evidence engage end users early enough in the evidence production process, that it facilitates decision making in policy and practice [37,40] In 2003, a study showed strategies to improve stakeholder engagement in LMICs were either not undertaken, or where they were undertaken, were not successful [6], so successfully carrying out this producer-user engagement servers to improve on the necessary task of building a critical mass of producers and users of HPSR evidence for the control of endemic diseases, and for overall health system strengthening in LMICs.…”
Section: Discussionsupporting
confidence: 69%
“…Details of the process and findings from the quantitative and qualitative situational analysis have been published and are available as open access. [35,36]…”
Section: Capacity Needs Assessment Workhopmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, in many countries, challenges remain. Research findings are not always properly integrated into policy and practice [5]. Above all, UHC is a complex endeavour at the crossroads of technique and politics, applied to health systems that are themselves complex and, thus, to some extent unpredictable [6,7].…”
Section: Introductionmentioning
confidence: 99%